The Adsorption of Mercury from Aqueous Solution on Durian (Durio zibethinus) Seed Immobilized Alginate - Intan Lestari; Silfia Devi Eka Putri Putri; Martina Asti Rahayu; Diah Riski Gusti (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
The increasing pollution of toxic heavy metals in the environment is an important issue worldwide. Heavy metal ions such as mercury have attracted special attention because of their high toxicity and long half-life which increase the potential to accumulate in the food chain and cause serious damage to the environment. The potential of an adsorbent durian (Durio zibethinus) seed immobilized alginate bead was carried out and used for the adsorption of Mercury in an aqueous solution. Adsorbents were characterized by FTIR, SEM, and XRF. FTIR analysis shows the functional groups of alcohol, amine, and carboxylic acid. Scanning Electron Microscopy shows that the surface morphology of durian seed powder of granules and durian seed immobilized in Ca-alginate of like as tissue eggs in an egg box shape. XRF analysis durian seed immobilized showed that Hg(II) ion adsorbed as much as 37%. The adsorption parameter of Hg(II) ion are pH at 6 with an adsorption capacity was 1.553 mg/g, contact time at 150 minutes with adsorption capacity was 2.880 mg/g, mass 0.1 g with adsorption capacity of 2.274 mg/g, and concentration 250 mg/g with adsorption capacity of 62.067 mg/g.